2017
DOI: 10.1161/circulationaha.117.030571
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Management, and Outcomes of Immune Checkpoint Inhibitor–Related Cardiotoxicity

Abstract: Although clinical trials reported a low incidence of immune-related cardiovascular adverse events,1 the number of published life-threatening cases of cardiotoxicity is increasing.2 In this descriptive observational analysis, we aimed to describe the clinical manifestations, management, and outcomes of patients who developed ICI-related cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
405
4
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 425 publications
(444 citation statements)
references
References 5 publications
14
405
4
21
Order By: Relevance
“…11 In a retrospective series of patients with ICI-induced cardiotoxicity, complete reversibility of left ventricular dysfunction was observed in 8 of 12 patients who received corticosteroids compared with 1 of 6 patients who did not. 96 Furthermore, in the retrospective and prospective multicenter registry of patients with ICI-induced myocarditis, higher starting doses of steroids were associated with lower serum troponin and lower rates of major adverse cardiac events. 94 Therefore, guidelines recommend initial methylprednisolone pulse dosing (1 g/day for 3-5 days).…”
Section: Cardiovascular Toxicitymentioning
confidence: 98%
“…11 In a retrospective series of patients with ICI-induced cardiotoxicity, complete reversibility of left ventricular dysfunction was observed in 8 of 12 patients who received corticosteroids compared with 1 of 6 patients who did not. 96 Furthermore, in the retrospective and prospective multicenter registry of patients with ICI-induced myocarditis, higher starting doses of steroids were associated with lower serum troponin and lower rates of major adverse cardiac events. 94 Therefore, guidelines recommend initial methylprednisolone pulse dosing (1 g/day for 3-5 days).…”
Section: Cardiovascular Toxicitymentioning
confidence: 98%
“…Among this number, 43% of deaths were linked to cardiac events and neurological complications 17 . Escudier et al showed that among patients who developed cardiotoxicity, 1/3 of deaths were caused by a cardiological problem 18 . Cardiac mortality is significantly more common in patients with conduction disorders and those treated with combined immunotherapy 18 .…”
Section: Cardiotoxicity In Clinical Practicementioning
confidence: 99%
“…Escudier et al showed that among patients who developed cardiotoxicity, 1/3 of deaths were caused by a cardiological problem 18 . Cardiac mortality is significantly more common in patients with conduction disorders and those treated with combined immunotherapy 18 . An association of fatal cardiac complications with anti‐CTLA‐4 and anti‐PD‐1/PD‐L1 has also been demonstrated.…”
Section: Cardiotoxicity In Clinical Practicementioning
confidence: 99%
“…Celý vyšetřovací algoritmus začíná elektrokardiogramem a echokardiografií, dvěma bazálními neinvazivními vyšetřovacími metodami. Pro myokarditidu mohou svědčit nespecifické změny vlny T, objevit se mohou i nové poruchy převodu, arytmie či elevace ST úseku, u kterých je pak nutné vyloučit akutní koronární syndrom [7]. Změny elektrokardiografie lze pozorovat u 40 % pacientů a až 70 % pacientů má sníženou ejekční frakci levé komory [6,8].…”
Section: Klinický Obraz a Dia Gnostikaunclassified